Self-healing epoxy coating synthesis by embedment of metal 2-methyl imidazole and acetylacetonate complexes with microcapsules - Ullah, Hafeez; Qureshi, Khurram Shehzad; Khan, Usama; Zaffar, Maryam; Yang, Yap Jen; Rabat, Nurul Ekmi; Khan, Muhammad Irfan; Saqib, Sidra; Mukhtar, Ahmad; Ullah, Sami; Mubashir, Muhammad; Bokhari, Awais; et al. (Chemosphere, 2021)
The restoration of mechanical properties is desired for creating the self-healing coatings with no corrosion capabilities. The encapsulation of epoxy resins is limited by various factors in urea and melamine formaldehyde microcapsules. An improved method was developed, where epoxy resin was encapsulated by individual wrapping of poly(melamine-formaldehyde) and poly(urea-formaldehyde) shell around emulsified epoxy droplets via oil-in-water emulsion polymerization method. The synthesized materials were characterized analytically. The curing of the epoxy was achieved by adding the [Ni/Co(2-MI)6].2NO3 as a latent hardener and iron acetylacetonate [Fe(acac)3] as a latent accelerator. Isothermal and non-isothermal differential scanning calorimetric analysis revealed lower curing temperature (Tonset = 116 °C) and lower activation energies (Ea ≈ 69-75 kJ/mol). The addition of microcapsules and complexes did not adversely alter the flexural strength and flexural modulus of the epoxy coatings. The adhesion strength of neat coating decreased from 6310.8 ± 31 to 4720.9 ± 60 kPa and percent healing increased from 50.83 to 67.45% in the presence of acetylacetonate complex at 10 wt% of microcapsules.
Keywords: Metal imidazole complex; tobolky; hydroxybutyráty; epoxidové pryskyřice; Pentanones; Epoxy resins; pentanony; Capsules; Adhesion strength; Self-healing; Hydroxybutyrates; Epoxy Resins; Flexural strength; Imidazoles; imidazoly; Melamine-urea-formaldehyde